Predictive role of PAR and LAR in refractory suppurative meningitis in infants - YaSong Gao; FangQi Hu (BMC, 2024)
Abstract Background Meningitis can be caused by a variety of pathogenic microorganisms, which can lead to higher mortality and disability rates. However, the clinical manifestations of suppurative meningitis are often atypical in infants and young children, which makes early clinical diagnosis difficult.PAR and LAR are considered as a novel inflammatory biomarker and have been applied in tumors, IgA nephropathy, sepsis. Objective To investigate the application of platelet/albumin (PAR) and lactate dehydrogenase/albumin (LAR) in refractory suppurative meningitis in infants. Methods The relevant clinical data of 107 children with suppurative meningitis were retrospectively analyzed, and were divided into common group (82 cases) and refractory group (25 cases) according to the severity of the disease according to the relevant clinical consensus. The relevant clinical data and laboratory examination of the children in the two groups were compared. The diagnostic value of PAR and LAR in children with refractory suppurative meningitis was analyzed and multivariate Logistic regression analysis was performed. Result The PAR of children with suppurative meningitis in refractory group was lower than that in common group (P < 0.05), while LAR was higher than that in common group (P < 0.05). Meanwhile, multivariate Logistic regression analysis showed that LAR and cerebrospinal fluid glucose ≤ 1.5mmo/L were risk factors for poor prognosis (OR > 1, P < 0.05). PAR was a protective factor (OR < 1, P < 0.05). Conclusion PAR and LAR can be used for early diagnosis of refractory suppurative meningitis in children as protective and risk factors, respectively.